If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6r + 11 = 15 + -1r Reorder the terms: 11 + 6r = 15 + -1r Solving 11 + 6r = 15 + -1r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add 'r' to each side of the equation. 11 + 6r + r = 15 + -1r + r Combine like terms: 6r + r = 7r 11 + 7r = 15 + -1r + r Combine like terms: -1r + r = 0 11 + 7r = 15 + 0 11 + 7r = 15 Add '-11' to each side of the equation. 11 + -11 + 7r = 15 + -11 Combine like terms: 11 + -11 = 0 0 + 7r = 15 + -11 7r = 15 + -11 Combine like terms: 15 + -11 = 4 7r = 4 Divide each side by '7'. r = 0.5714285714 Simplifying r = 0.5714285714
| x^2+4x-94=0 | | 4-2(x+5)=4 | | 7(b-2)=4 | | 2(10-3d)+80= | | 3x+2-x=12 | | F(x+8)=3(x+8)-9 | | 7=8(r-6) | | 7(v+4)-3v=2(2v+2)-12 | | 0.04x^2-3.5x+100=10 | | 8x+17=5x+23 | | 18x+54=252 | | y=0.7x-3.6 | | 10+11x=-30+x | | -6(i-3)=2 | | 4x+6(x-4)=16 | | 22+4x=9x+2 | | -9(-6)-5(2)=12 | | 154x=462 | | -9(3)-5(-6)=12 | | 5x+5y+6z-2x+z-8y= | | 4=7(r-3) | | -36=3(x-3)-6x | | 4-5y=-20 | | 9=6(q-6) | | 0=-0.09+1.1x | | 7x-2(4x+23)+12= | | 5+7=2x | | -6(-3)-7(2)=4 | | 2(y+5)-4y=16 | | 3n-n+5= | | 5+2(2x-5)=-2+3(x-2) | | 2x-5x=-1-5 |